PENGARUH LINGKUNGAN KERJA NON FISIK DAN KETERLIBATAN ORGANISASIONAL TERHADAP RETENSI KARYAWAN - Astuti, Desak Made Yuni; Dewi, A.A. Sagung Kartika (E-Jurnal Manajemen; Vol 8 No 7 (2019), 2019)
The purpose of this study was to determine the effect of non-physical work environment and organizational involvement on employee retention. This research was conducted at Kumala Hotel Legian Beach. The population of this study was all permanent employees totaling 148 people and using the Slovin formula to obtain a sample of 108 respondents. The sampling technique used in this study is disproportionate stratified random sampling. The method of data collection is done by means of interviews and surveys with tools in the form of questionnaires. The data analysis technique used is multiple linear regression analysis which is processed using SPSS. The results of this study indicate that all research hypotheses are acceptable. Non-physical work environment has a positive and significant effect on employee retention. Organizational involvement has a positive and significant effect on employee retention. The better the non physical work environment and organizational involvement, the higher the employee retention rate. Keywords : non physical work environment, organizational involvement, employee retention